2017
DOI: 10.1371/journal.pone.0169251
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Reoffending Using the Structured Assessment of Violence Risk in Youth (SAVRY): A 5-Year Follow-Up Study of Male Juvenile Offenders in Hunan Province, China

Abstract: BackgroundJuvenile violent offending is a serious worldwide public health issue.ObjectiveThe study examined whether the Structured Assessment of Violence Risk in Youth (SAVRY) can be used to predict violent reoffending in Chinese male juvenile offenders, and to determine which risk/protective domains (items) are associated with violent recidivism.MethodsA total of 246 male juvenile offenders were recruited. SAVRY domains were scored by trained raters based on file review and interviews with participants and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
8
2
1
Order By: Relevance
“…The predictive validity of the SAVRY Protective factors has yielded some positive findings [15,17], such as inversely predicting general reoffending [18], violence [17], and violent and general reoffending [19,20]. Some studies have shown mixed findings, such as predictive validity for only general reoffending [21], nonviolent reoffending [22], or only violent reoffending [14,23]. Further, a recent systematic review found that SAVRY Protective factors were not significantly related to violence or offending (k = 14 studies) [24].…”
Section: Existing Research On Measures Of Protective Factorsmentioning
confidence: 99%
“…The predictive validity of the SAVRY Protective factors has yielded some positive findings [15,17], such as inversely predicting general reoffending [18], violence [17], and violent and general reoffending [19,20]. Some studies have shown mixed findings, such as predictive validity for only general reoffending [21], nonviolent reoffending [22], or only violent reoffending [14,23]. Further, a recent systematic review found that SAVRY Protective factors were not significantly related to violence or offending (k = 14 studies) [24].…”
Section: Existing Research On Measures Of Protective Factorsmentioning
confidence: 99%
“…Results from various studies suggest that the SAVRY has a small to large effect size for the prediction of violent reoffending (Chu et al, 2016; Dolan & Rennie, 2008; Hilterman et al, 2014; Lodewijks et al, 2008; McGowan et al, 2011; Zhou et al, 2017). However, most of the studies reporting large effect sizes were conducted in Europe and North America (AUC = 0.69–0.86); with the Singaporean (Chu et al, 2016) and Chinese (Zhou et al, 2017) studies reporting smaller effect sizes (AUC = 0.63–0.65 and AUC = 0.68 respectively). The authors of the Singapore study observed that the SAVRY Total Score was lower than that of Western studies, and the SAVRY Protective Total Score was higher.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have indicated that SAVRY protective factors are associated with reduced likelihood of reoffending (i.e., Gammelgård, Koivisto, Eronen, & Kaltiala-Heino, 2015;Guy, 2008;Lodewijks, de Ruiter, & Doreleijers, 2010;McGowan, Horn, & Mellott, 2011;Ortega-Campos, García-García, & Zaldívar-Basurto, 2017;Rennie & Dolan, 2010;Schmidt, Campbell, & Houlding, 2011;Shepherd, Luebbers, Ogloff, Fullam, & Dolan, 2014;Vincent, Guy, Gershenson, & McCabe, 2012). However, other studies have failed to find significant associations (i.e., Hilterman, Nicholls, & van Nieuwenhuizen, 2014;Klein, Rettenberger, Yoon, Köhler, & Briken, 2015;Penney, Lee, & Moretti, 2010;Perrault, Vincent, & Guy, 2017;Viljoen et al, 2008), or have yielded mixed results (i.e., Chu, Goh, & Chong, 2016;Dolan & Rennie, 2008;Vincent, Chapman, & Cook, 2011;Zhou, Witt, Cao, Chen, & Wang, 2017). Recently, a systematic review aggregated these findings (Dickens & O'Shea, 2017).…”
mentioning
confidence: 99%